2004
DOI: 10.1084/jem.20040920
|View full text |Cite
|
Sign up to set email alerts
|

Bruton's Tyrosine Kinase Is Essential for Human B Cell Tolerance

Abstract: Most polyreactive and antinuclear antibodies are removed from the human antibody repertoire during B cell development. To elucidate how B cell receptor (BCR) signaling may regulate human B cell tolerance, we tested the specificity of recombinant antibodies from single peripheral B cells isolated from patients suffering from X-linked agammaglobulinemia (XLA). These patients carry mutations in the Bruton's tyrosine kinase (BTK) gene that encode an essential BCR signaling component. We find that in the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
169
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(176 citation statements)
references
References 51 publications
7
169
0
Order By: Relevance
“…1B) implicate Btk signaling in the termination of V(D)J recombination activity upon productive Ig L chain rearrangement in immature B cells. This would be consistent with the finding that peripheral B cells from X-linked agammaglobulinemia patients, who have mutations in the Btk gene, show a distinct Ab repertoire consistent with extensive secondary V(D)J recombination (49).…”
Section: Discussionsupporting
confidence: 90%
“…1B) implicate Btk signaling in the termination of V(D)J recombination activity upon productive Ig L chain rearrangement in immature B cells. This would be consistent with the finding that peripheral B cells from X-linked agammaglobulinemia patients, who have mutations in the Btk gene, show a distinct Ab repertoire consistent with extensive secondary V(D)J recombination (49).…”
Section: Discussionsupporting
confidence: 90%
“…1) and the inhibition of PI3K with inhibitors (29) result in a phenotype compatible with a role for basal signaling in suppressing Rag induction. Of interest, a recent report showed that a high percentage of B cells that "squeak" through development in human X-linked agammaglobulinemia, a disorder characterized by mutations in btk, have a peripheral B cell repertoire enriched for autoimmune BCRs (68). The authors propose that inefficient signaling through the BCR may favor the development of autoreactive B cells, which is consistent with the model proposed here.…”
Section: Discussionsupporting
confidence: 78%
“…BCR-mediated signaling and Toll-like receptor-mediated signaling in precursor B cells are important for the removal of autoreactive B-cell receptors, as patients with genetic defects in BTK or MyD88 have been shown to have increased number of B cells carrying autoreactive BCRs. 26,27 Because the CD19 complex is important for signaling by the BCR, it might have a similar role in the removal of B cells carrying autoreactive B-cell receptors. In our cohort of 30 carriers of a CD19 gene mutation, we did not find increased autoimmunity or increased levels of ANAs.…”
Section: Discussionmentioning
confidence: 99%